Antibacterial effects of trisubstituted quinazoline derivatives - Jantová, S; Greif, G; Spirková, K; Stankovský, S; Oravcová, M (Folia microbiologica, 2000)
Five trisubstituted quinazolones and eight trisubstituted quinazoline-4-thiones have been tested for antibacterial effects by a microdilution method. Four derivatives exerted a significant effect on E. coli, P. aeruginosa, S. aureus and B. subtilis (IC50 < 100 mg/L). In the bacterium P. aeruginosa six quinazolines showed a higher antibacterial effect than ampicillin. The most sensitive to the effects of the quinazolines was S. aureus; a concentration of 100 mg/L of six derivatives induced a bacteriostatic effect on S. aureus. The quinazoline-4-thiones were generally more active than the quinazolones. All the tested concentrations of the four most effective quinazolines influenced the specific growth rate.
Keywords: Bacillus subtilis; antibakteriální látky; Microbial Sensitivity Tests; Bacteria; Quinazolines; Pseudomonas aeruginosa; chinazoliny; Escherichia coli; Anti-Bacterial Agents; Staphylococcus aureus; mikrobiální testy citlivosti